Common bile duct stones: its different aspects of presentation and management - kumar, Nishant (International Surgery Journal, 2020)
Background: Common bile duct (CBD) stone management is a commonly occurring potential challenge for surgeons. Methods: A total of 38 patients who was admitted in admitted in surgery Department of Sri Ram Institute of Medical Sciences, Bareilly UP during the period of March 2019 to September 2019 were studied. The diagnosis was made using USG MRCP, relevant blood investigations. Patients were managed based on radiological findings by the best possible way and expertise available. Results: Out of the 38 patients, 14 (37.14%) were male and 24 (62.85%) were female. The mean age for male was 50.92 years and for female, it was 51.74 yrs. Most of the patients had pain abdomen and /or jaundice with a mean total bilirubin of 3 mg/dl. Patients are managed either by ERCP or by surgery (open/laparoscopic). Mortality is nil but morbidity is more for open procedures. Conclusions: There can be no definite algorithm for the management of CBD stones as the patients’ age, underlying general condition being the only standardizable factor with facilities for endoscopic, laparoscopic management being variably available from institution to institution and hence, necessitating tailoring the management of CBD stones depending upon the Institution’s resources.